ABDOMINAL OBESITY PATTERN AMONG VARIOUS ETHNIC GROUPS PRESENTING WITH ACUTE CORONARY SYNDROME - Mahmood, Mazhar; Ashraf, Tariq; Memon, Mohammad Anis; Achakzai, Abdul Samad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Abdominal obesity is an increasing public health problem and is associated with a number of cardiovascular risk factors. The aim of this study was to determine the frequency of abdominal obesity and associated risk factors in patients of various ethnic groups presenting with acute coronary syndrome. Methods: A total of 477 patients presenting with acute coronary syndrome to the National Institute of Cardiovascular Diseases, Karachi were studied. The sample was divided into 5 major ethnic groups, Muhajir, Punjabi, Sindhi, Pathan, Baluchi and Others. Waist circumference of each patient was taken at the level of iliac crest and abdominal obesity was defined according to the International Diabetes Federation criteria of 2005 for South Asians as waist circumference ‰¥ 90 Cm in males and ‰¥80 Cm in females. Patients were also assessed for diabetes mellitus, hypertension, smoking, low HDL and elevated triglycerides. Results: Out of 477 patients (355 males, 122 females), abdominal obesity was present in 318 (67%) patients, 62% of males and 81% of females were obese. Abdominal obesity was 62% in Muhajir, 78% in Punjabi, 67% in Sindhi, 68% in Pathan, 59% in Baluchi and 64% in others. Hypertension was present in 46%, Diabetes mellitus in 32%, Smoking in 33%, Low level of High density lipoprotein in 85.5% and raised triglycerides in 35% of patients. Conclusion: Abdominal obesity in Punjabi ethnic group is more common as compared to other ethnic groups. Low level of high density lipoprotein is almost universally present in patients with acute coronary syndrome. Keywords: Abdominal obesity, Acute coronary syndrome, Waist circumference, Cardiovascular risk factors